(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The need to improve the teaching of business subjects necessitated this study to ascertain the level of utilization of modern instructional materials for teaching business subject in secondary schools in Anambra State, Nigeria. One research question guided the study and three null hypotheses were tested. Descriptive survey research design was adopted and 249 male and female business subjects teachers were studied without sampling. A structured questionnaire was used for data collection. The questionnaire was validated by three experts in the field of business education and measurement and evaluation from the Faculty of Education, Nnamdi Azikiwe University, Awka. A total of 249 copies of questionnaire were distributed to the respondents, 241 copies were correctly filled, retrieved and used for data analysis. Data collected was analyzed using mean and standard deviation to determine the homogeneity of the respondents’ ratings while t-test was used to test the null hypothesesat 0.05 level of significance. Findings revealed that business subjects teachers rarely utilized modern instructional materials for teaching business subjects. The findings also showed that school location and gender were significant factors on respondents’ ratings of level of utilization of modern instructional materials while years of experience was not a significant factor. The researchers recommended among others that business subjects teachers should endeavour to utilize available modern instructional materials inthe teachingof business subjects to enable students acquire relevant skills and competencies for gainful employment or self-employment.